Valverde Burgos,Enrique Alexander(2023)ELABORACIÓN DE BARRAS DE CHOCOLATE A PARTIR DE ALMENDRAS DE CACAO DE MONTAÑA (Theobroma bicolor Hump & Bonpl L.) CON ADICIÓN DE PASTA DE FRUTAS DESHIDRATADAS DE NARANJA (Citrus x sinesis) Y MANGO (Magnifera indica).Quevedo.UTEQ.98p. - Valverde Burgos , Enrique Alexander (2023)
The genus Theobroma is one of the most important plant species, which currently has 22 known species, being one of those with the highest rate of production and cultivation worldwide, one of the not so common species is mountain cocoa (Theobroma bicolor Hump. & Bonpl. L.) also known by various names such as Pataxte, white cocoa, wild cocoa, mountain cocoa. The objective of this research is to evaluate a proposal for a chocolate bar with the use of cocoa almonds incorporating factor A of cocoa concentrations of 75, 50 and 100%, together with the incorporation of factor B of dehydrated fruit paste. of orange (Citrus x sinesis) and mango dehydrated fruit paste (Magnifera indica) contributing to the development evaluating its performance based on organoleptic, sensory and microbiological analysis parameters obtaining in the end a gourmet chocolate bar worthy of high quality aroma, Se was able to determine, based on the hedonic test of acceptability of the chocolate bars with the help of a semi-trained tasting panel, that treatment T2 (75% Theobroma bicolor cocoa and fine aroma cocoa 30% dehydrated orange paste) behaved satisfactory being the best study treatment.